VLDLR disturbs quiescence of breast cancer stem cells in a ligand-independent function - Yang, Mengying; Zhan, Yajing; Hou, Zhijie; Wang, Chunli; Fan, Wenjun; Guo, Tao; Li, Zhuoshi; Fang, Lei; Lv, Shasha; Li, Sisi; Gu, Chundong; Ye, Mingliang; et al. (Frontiers in Oncology, 2022)
Breast cancer stem cells are responsible for cancer initiation, progression and drug resistance, however, effective targeting strategies against the cell subpopulation are still limited. Here, we unveil two splice variants of very low density lipoprotein receptor, VLDLR-I and -II, are highly expressed in breast cancer stem cells. In breast cancer cells, VLDLR silencing suppresses sphere formation abilities in vitro and tumor growth in vivo. We find that VLDLR knockdown induces transition from self-renew to quiescence. Surprisingly, ligand-binding activity is not involved in the cancer-promoting functions of VLDLR-I and -II. Proteomic analysis reveals that citrate cycle and ribosome biogenesis related proteins are upregulated in VLDLR-I and -II overexpressed cells, suggesting VLDLR dysregulation is associated with metabolic and anabolic regulation. Moreover, high expression of VLDLR in breast cancer tissues correlates poor prognosis of patients. Collectively, these findings indicate that VLDLR may be an important therapeutic target for breast cancer treatment.